CDNA microarray analysis identifies NR4A2 as a novel molecule involved in the pathogenesis of Sjögren's syndrome. (21st July 2017) - Takahashi, H; Tsuboi, H; Asashima, H; Hirota, T; Kondo, Y; Moriyama, M; Matsumoto, I; Nakamura, S; Sumida, T
Summary: To examine genes expressed specifically in labial salivary glands (LSGs) of patients with Sjögren's syndrome (SS) in comparison with those of patients with immunoglobulin (Ig)G4-related disease (IgG4-RD), and to identify the genes involved in the pathogenesis of SS. Gene expression in LSGs of SS patients, IgG4-RD patients and healthy controls (HC) was analysed by cDNA microarray. Quantitative polymerase chain reaction (qPCR) was used to validate the up-regulation of differentially expressed genes (DEGs) in SS. Protein production of the validated gene in LSGs was examined by immunofluorescence (IF) assay. The association of molecular functions of the gene with the pathological conditions in SS was examined using peripheral blood lymphocytes. Among 1320 DEGs up-regulated in SS, qPCR confirmed the up-regulation of NR4A2 in LSGs of SS compared with IgG4-RD. IF staining showed higher production of NR4A2 in nuclei of CD4 + T cells and interleukin (IL)-17-producing cells in LSGs of SS, compared with IgG4-RD. Over-expression of NR4A2 mRNA was observed in peripheral CD4 + T cells of SS patients, compared with HC. Nuclear NR4A2 expression in T helper type 17 (Th17)-polarized CD4 + T cells determined by cellular IF was significantly higher in SS than in HC. Importazole, an inhibitor of importin-β, inhibited nuclear transport of NR4A2 and Th17 polarization along with IL-21 expression in naive CD4 + T cells under Th17-polarizing conditions, but did not alter retinoic acid receptor-related orphan receptor C (RORC) expression. NR4A2 seems to promote Th17 polarization via increased expression and intranuclear localization in CD4 + T cells of SS patients, which could play a critical role in the pathogenesis of SS. Graphical Abstract: